Large Vehicle Service Service Application at M. Zakky Workshop Based on Android - Eko Saputra Apriansyah; Anisya Sonita (Penerbit Jurnal Indonesia, 2022)
M. Zakky's workshop is one of the car repair shops in Bengkulu City that handles large car vehicle services. The vehicle service process is carried out at the workshop location where consumers come directly to deliver the car to be serviced. Most consumers experience damage or strike in areas far from the workshop location, making it difficult for these consumers to deliver the car to the workshop. To make it easier for consumers, the workshop wants to provide services outside the workshop location. By utilizing current technology, it is possible to help the workshop by using an application that can be used using a smartphone. An application that can be used to view a complete list of service services with the cost of processing and can also see a list of spare parts that are sold. Consumers can order service services by selecting one of the service items provided or placing an order for spare parts and the workshop will directly go to the consumer to make repairs or install the spare parts ordered. The application for ordering large vehicle services at the M. Zakky workshop based on android was built using the java and xml programming languages ​​with the help of android studio software. The application consists of 3 parts, namely user, admin and mechanic. The user application is for general users who can order workshop service services, the admin application is used to process service data, while the mechanic application is used to receive orders that have been made by the user. The application can run well on the android platform with a firebase database so it requires an internet connection to be able to use it.